[Koperta ze stamplem i znaczkiem: Lech Wałęsa] . Envelope with stamp and watermark: Lech Wałęsa - Poczta Solidarność Walcząca. (Poczta Solidarność Walcząca, 1986)
Envelope with a b&w print on white paper, rounded black watermark, and col. stamp with perforation. For stamp see record "Ofiarom Grudnia 1970 - Gdynia". Envelope consists of a b&w print, a watermark and a stamp. The print represents a protrait of Lech Wałęsa. The watermark represents the logo of "Solidarność Walcząca" (letters "s" and "w" merged), with captions "Poczta Solidarność Walcząca", "Rzeczpospolita Solidarna" and "Wrocław". Stamp by S. Małecki, issued in 1981, represents the Gdynia monument to the workers killed during street clashes in December 1970 , priced 6,50 + 1 zł.